2007
DOI: 10.1002/jnr.21215
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced susceptibility of Prnp‐deficient mice to kainate‐induced seizures, neuronal apoptosis, and death: Role of AMPA/kainate receptors

Abstract: Normal physiologic functions of the cellular prion protein (PrPc) are still elusive. This GPI-anchored protein exerts many functions, including roles in neuron proliferation, neuroprotection or redox homeostasis. There are, however, conflicting data concerning its role in synaptic transmission. Although several studies report that PrPc participates in NMDA-mediated neurotransmission, parallel studies describe normal behavior of PrPc-mutant mice. Abnormal axon connections have been described in the dentate gyru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
89
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(102 citation statements)
references
References 126 publications
12
89
0
1
Order By: Relevance
“…In addition, both lines showed deficits in synaptic transmission (Collinge et al, 1994;Herms et al, 1995) and increased sensitivity to oxidative stress (Brown et al, 2002). Recent studies indicate that these mice also show increased susceptibility to glutamate excitotoxicity (Khosravani et al, 2008a;Rangel et al, 2007;Walz et al, 1999;Walz et al, 2002) as a result of changes in the expression of glutamate receptor subunits (Khosravani et al, 2008a;Lledo et al, 1996;Rangel et al, 2007). More recently, a conditional knockout of PrP c has been generated (Mallucci et al, 2002).…”
Section: Prnp-deficient Micementioning
confidence: 99%
See 1 more Smart Citation
“…In addition, both lines showed deficits in synaptic transmission (Collinge et al, 1994;Herms et al, 1995) and increased sensitivity to oxidative stress (Brown et al, 2002). Recent studies indicate that these mice also show increased susceptibility to glutamate excitotoxicity (Khosravani et al, 2008a;Rangel et al, 2007;Walz et al, 1999;Walz et al, 2002) as a result of changes in the expression of glutamate receptor subunits (Khosravani et al, 2008a;Lledo et al, 1996;Rangel et al, 2007). More recently, a conditional knockout of PrP c has been generated (Mallucci et al, 2002).…”
Section: Prnp-deficient Micementioning
confidence: 99%
“…Lastly, pioneering electrophysiological studies (using PrP c knockout slices) by Collinge established that PrP c participates in long-term potentiation (Collinge et al, 1994;Curtis et al, 2003;Maglio et al, 2006). More recently, it has been shown that the absence of PrP c alters the expression of several neurotransmitter receptors (see (Maglio et al, 2004;Rangel et al, 2007) for examples). Thus, Prnp 0/0 mice show increased neuronal excitability as well as enhanced glutamate excitotoxicity by modulation of NMDA as well as kainate receptors (Khosravani et al, 2008b).…”
Section: Introductionmentioning
confidence: 99%
“…Prnp 0/0 mice have a normal development and are completely resistant to prion infections (5) and, although useful in the study of disease pathogenesis, have heightened curiosity as to PrP C 's function. Reported phenotypes in Prnp 0/0 mice are disparate and sometimes subtle: these include altered circadian rhythms (6,7), sensitivity to oxidative stress (8), excitability of hippocampal neurons (9,10), sensitivity to seizure (11,12), age-related behavioral deficits (13)(14)(15), deficits in olfaction (16), and altered maintenance of the peripheral nervous system (17). The nonlethal effect of PrP C -deficiency has provoked interest in the concept of functional degeneracy, with a hypothetical PrP functional homolog being deduced from genetic data and termed "π" (18,19).…”
mentioning
confidence: 99%
“…Moreover, after ischemic or traumatic brain injury, lesion size is larger in Prn-p 0/0 compared to wild-type mice (Hoshino et al, 2003;McLennan et al, 2004;Sakurai-Yamashita et al, 2005;Spudich et al, 2005). Finally, Prn-p 0/0 mice are more susceptible to kainate-induced seizures (Rangel et al, 2007) and their retinal photoreceptors are more prone to light-induced degeneration (Frigg et al, 2006).…”
Section: Function Of Prp Cmentioning
confidence: 99%